ANALISIS PENGARUH CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH PADA PT. BANK SINARMAS KANTOR CABANG MATARAM - Dewa Made Suparwata (Master of Management, Mataram University, 2017)
Every company aspires rapid growth in each business unit lived. One thing you can do is to pay attention to aspects of customer loyalty. The purpose of research is to analyze and prove the influence of Trust, Commitment Company, Communication, Conflict Management Customer Loyalty At PT. Bank Sinarmas branch office Mataram. This type of research is the study of causality. The sampling technique used was purposive sampling as many as 170 customers. Analysis of data using multiple linear regression analysis model. The results showed that (1) There is a significant influence of Confidence in Bank Sinarmas Customer Loyalty Branch Mataram. (2) There is a significant influence of the Company's commitment to Customer Loyalty Branch Bank Sinarmas Mataram. (3) There is a significant influence on the Communication on Bank Sinarmas Customer Loyalty Branch Mataram. (4) There is a significant influence of the Conflict Management to Customer Loyalty Branch Bank Sinarmas Mataram. For the management of Bank Sinarmas Branch Mataram, to improve customer loyalty is with the aspect of trust, Corporate Commitment, Communication and Conflict Management for all aspects of this significant effect on customer loyalty. Keywords: Trust, Commitment Company, Communication, Conflict Management, Customer Loyalty